Fenichel's clinical pediatric neurology : a signs and symptoms approach - Fenichel, Gerald M.; Piña-Garza, J. Eric (Elsevier/Saunders, 2013)
Confidently diagnose and manage primary neurologic disorders of childhood with actionable, step-by-step assistance from Fenichel's Clinical Pediatric Neurology! A signs-and-symptoms-based approach - with consideration of each presenting symptom in terms of differential diagnosis and treatment - mirrors the way you would typically evaluate and manage a patient. A practical and well-organized introduction to pediatric neurology, this is an ideal resource for board exam preparation, office use, and reference during residency. Quickly identify the progression of each neurological disease. Extensive coverage clearly defines age at onset, course of illness, clinical features, and treatment options. Evaluate and manage even the most difficult neurodegenerative disorders-including those caused by inborn errors of metabolism - with the aid of differential diagnosis tables and treatment algorithms. Search crucial information at a glance. An organization by neurological signs and symptoms, together with a user-friendly, highly templated format allows for quick and easy reference. Rely on it anytime, anywhere!.